Cover Image, Volume 67, Issue 12. Issue 12 (31st October 2018) - Toh, Guat Yee; Ong, Hui Lin; Bindumadhavan, Kartick; Doong, Ruey‐an
Abstract : The cover image is based on the Research Article Physicochemical properties of reduced graphite oxide conglomerated polyethylene nanocomposites by Guat Yee Toh et al., DOI: 10.1002/pi.5687 . Supported by Ministry of Science and Technology, Taiwan. Project numbers MOST 105‐2113‐M‐009‐023‐MY3 and MOST 107‐2221‐E‐007‐113‐MY3. Abstract : The cover image is based on the Research Article Physicochemical properties of reduced graphite oxide conglomerated polyethylene nanocomposites by Guat Yee Toh et al., DOI: 10.1002/pi.5687 . Supported by Ministry of Science and Technology, Taiwan. Project numbers MOST 105‐2113‐M‐009‐023‐MY3 and MOST 107‐2221‐E‐007‐113‐MY3.